1997
DOI: 10.1097/00000658-199710000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Cardiac Valve Surgery Improves Patient Satisfaction While Reducing Costs of Cardiac Valve Replacement and Repair

Abstract: ObjectiveThis study compares the quality of valve replacement and repair performed through minimally invasive incisions as compared to the standard operation for aortic and mitral valve replacement. Summary Background DataWith the advent of minimally invasive laparoscopic approaches to orthopedic surgery, urology, general surgery, and thoracic surgery, it now is apparent that standard cardiac valve operations can be performed through very small incisions with similar approaches. MethodsEighty-four patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
376
1
15

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(395 citation statements)
references
References 5 publications
3
376
1
15
Order By: Relevance
“…Reductions in postoperative bleeding and transfusion requirements after minimally invasive mitral valve surgery are likely due to smaller incisions and less extensive mediastinal dissection (5,7,8,(17)(18)(19)(20)(21)(22)(23). Other centers, including our own, have also demonstrated significant associations between less invasive mitral valve surgery and reduced bleeding and transfusion (7).…”
Section: Comparison To Sternotomy Approachmentioning
confidence: 60%
See 2 more Smart Citations
“…Reductions in postoperative bleeding and transfusion requirements after minimally invasive mitral valve surgery are likely due to smaller incisions and less extensive mediastinal dissection (5,7,8,(17)(18)(19)(20)(21)(22)(23). Other centers, including our own, have also demonstrated significant associations between less invasive mitral valve surgery and reduced bleeding and transfusion (7).…”
Section: Comparison To Sternotomy Approachmentioning
confidence: 60%
“…P r o c e d u r a l c o s t a n d r e s o u r c e u t i l i z a t i o n a r e increasingly important factors in evaluating different treatments. Multiple groups demonstrated that shorter hospital stays after less invasive mitral valve surgery translate to cost saving ranging from 7% to 34% (18,19,33). Further economic benefit may stem from lower rehabilitation requirements and lower rates of early rehospitaliztion (7,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A-Upper Partial Sternotomy (J-shaped Hemisternotomy) approach: It is considered the most common approach in MIAVR nowadays (L. H. Cohn et al, 1997;Cosgrove & Sabik, 1996). Skin incision would be 6-8 cm in the midline over the upper part of the sternum extending from the suprasternal notch up to the 3 rd or 4 th intercostal space.…”
Section: Minimally Invasive Aortic Valve Surgeries (Miavr)mentioning
confidence: 99%
“…Potential advantages include improved cosmetic results and comfort for the patient as well as shorter hospital stays, which impact on total cost 9 . Approaches that are widely used for the pediatric population include the anterior thoracotomy 5,8,[10][11] and upper or lower minimal access sternotomy [12][13][14] , with or without video assistance.…”
Section: Introductionmentioning
confidence: 99%